Grains and Grain Products - Kurbanbaeva Gulshad Sarsenbaevna; Masharipova Bakhor Ixtiyor qizi (Genius Journals, 2023)
Cereal crops are the most important group of agricultural crops grown for grain, cereal grain is the main food product for humans, raw material for many branches of industry, as well as fodder for livestock. This article contains sufficient information on cereal crops, their types and pest control.
Keywords: Grain; caryopsis; Pesticides; fungicides